Idealized Motherhood: Examples of the Gendered Worldview of the Pastoral Letters - Huizenga, Annette Bourland (Interpretation, 2021)
In the Pastoral Letters, the roles and practices of mothering in a domestic household serve as benchmarks for the general instructions on how “one ought to behave in the household of God” (1 Tim 3:15). This article examines several passages in 1–2 Timothy and Titus in which the author employs an idealized and stereotypical view of motherhood in order to persuade female believers to fulfill this socially-appropriate condition and to restrict them from leadership positions in the community.